A retrospective study of COVID‑19 in patients with metabolic dysfunction‑associated fatty liver disease (MAFLD) in Saudi Arabia - Ghulais, Mesk Saleh Ali; Saidi, Hasni Idayu; Khaza'ai, Huzwah; Belal, Khaled; Daut, Ummi Nadira; Muthanna, AbdulRahman; Md Razip, Nurliyana Najwa (Life Sciences, Medicine and Biomedicine, 2026)
Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD) has emerged as a significant comorbidity in COVID-19 patients. This retrospective case-control study included 224 COVID-19 patients (112 with MAFLD and 112 without MAFLD) for clinical and biochemical evaluation. Data collection followed a consecutive sampling protocol was performed using a random number generator on the list of eligible patients, incorporating all patients who met the inclusion criteria during the study period to ensure a representative and unbiased clinical sample. MAFLD patients demonstrated considerably worse clinical profiles compared to controls, with higher obesity rates (78% vs. 22%), prolonged hospitalization (84% vs. 16%), and more severe COVID-19 presentations (45% vs. 55%). During infection, significant differences were observed in AST, CRP, HSI, and AST/ALT ratio (p